RESPONS PERTUMBUHAN DAN KOMPOSISI RANTAI PANJANG POLYISOPRENOID SEMAI BERJENIS SEKRESI Xylocarpus granatum Koenig. TERHADAP SALINITAS - Nurfalah Siregar; Mohammad Basyuni; Budi Utomo (Program studi Kehutanan USU, 2015)
Growth response and composition of long chain polyisoprenoid of minor secretor Xylocarpus granatum Koenig seedlings to salinity was studied in the greenhouse, Faculty of Agriculture and Laboratory of Forest Ecology, University of Sumatera Utara. Research was started from July to November 2014. This study used five levels of salinity, namely 0%, 0,5%, 1,5%, 2% and 3% X. granatum where seedlings were grown for 3 months. The best result was obtained at 0,5% salinity, seedling height at 0,5% salinity, diameter seedlings in salinity 0%, number of leaves at 2% salinity, leaf area at 2% salinity, wet weight of sample was at 0,5%, wet weight shoot at a salinity of 0,5%, wet weight of the stem at a salinity of 0,5%, root dry weight in salinity 0%, shoot dry weight at 2% salinity, stem dry weight at 0,5% salinity, and sample dry weight at 0,5% salinity. Chromatogram showed that X. granatum seedlings contained dolichol in the leaves and roots under 0% salinity concentration.Keywords: Mangrove, morphology, polyisoprenoid, salinity, X. granatum Koenig.